Jean-Louis Schonberg, Federico García Lorca. L'homme. L'œuvre. Librairie Plon, Paris, 1956; 362 pp. - Blanco Aguinaga, Carlos (El Colegio de México, 1959)
Se reseñó el libro: Federico García Lorca. L'homme. L'œuvre.